(untitled) (Revista de Estudios Europeos, 2026)
This work explores the main legal and procedural challenges in implementing a child friendly justice system within the European Union. Building on the recognition of children as rights holders, it underscores the need to transform judicial proceedings to ensure their effective access to justice, meaningful participation, and comprehensive protection. The study focuses on key procedural dimensions such as the child’s right to be heard, the right to receive information, protection from revictimization, and the need for specialized legal professionals. The analysis advocates for an inclusive, rights-based, and human-centred model of justice aligned with the best interests of the child